Book review essay:Protecting the environment of the final frontiers - Koivurova, Timo (Global Environmental Politics, 2017)
Review of Howkins, Adrian. 2016. The Polar Regions: An Environmental History. Cambridge: Polity Press. Pincus, Rebecca, and Saleem H. Ali, eds. 2015. Diplomacy on Ice: Energy and the Environment in the Arctic and the Antarctic. New Haven: Yale University Press. Stone, David P. 2015. The Changing Arctic Environment: The Arctic Messenger. Cambridge: Cambridge University Press.